Identifying Transformative Sequences in the Psychotherapeutic Interaction With Chinese Adolescents With Depression: A Conversation Analysis Approach - Ma, Wen; Fan, Xingang; Zhang, Shuai (Frontiers in Psychology, 2022)
Previous studies seldom touch on aspects of psychotherapeutic encounters between therapists and clients with particular disorders (such as depression). Little attention has been paid to the sequence organization of psychotherapeutic interaction between therapists and clients with depression in Chinese medical settings. By adopting conversation analysis, we investigated the specifics of psychotherapeutic encounters, specifically, the transformative sequences of psychotherapeutic interaction between therapists and Chinese adolescents with depression. We found three patterns of the transformative sequences in our data: P-T-R1-TP-R2 (Prior action-Target action-Response1-Third position-Response2), P-T1-S-T2-R (Prior action-Target action1-Silence-Target action2-Response), and P-T1-R1-T2-R2 (Prior action-Target action1-Response1-Target action2-Response2). We further identified another realm of clients’ experience (i.e. cognition) and described how the sequential organization of therapists’ actions facilitates the momentary transformation of clients’ experience (i.e. the transformation of referents, emotions, relations, and cognition) in the psychotherapeutic processes. This study not only adds to the CA study on the transformative sequences in psychotherapeutic interaction, but also sheds some light on the study of how therapists transform clients’ experience in Chinese psychotherapeutic interaction.